Phononology-syntax analogies - Anderson, John M. (John Mathieson), 1941- (Oxford : Oxford University Press, 2011)
This volume looks at the degree to which analogies between syntax and phonology result from their being representational subsystems within the overall system of language, at why they sometimes break down, and at how far semantic and phonetic properties limit such analogies.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Grammar, Comparative and general -- Syntax; Grammar, Comparative and general -- Phonology; Structural linguistics